Pemenuhan Hak dan Kebutuhan Narapidana Perempuan di Lembaga Pemasyarakatan - Yustina Mariana Neta; Hery Fernandez Butar Butar (Institut Agama Islam Negeri Bengkulu, 2022)
Human rights are fundamental rights that must be given by the state to its citizens, including prisoners. The granting of these rights must of course be fair and proportional. In this case, for female prisoners who naturally have characteristics that are not possessed by men, namely menstruation, pregnancy, childbirth and breastfeeding, it is necessary to fulfill special needs that must be considered for their survival. Corrections in this case need to apply treatment that is in accordance with the needs of female prisoners, so special policies are also needed as the foundation of treatment. However, there is no national regulation in Indonesia that specifically regulates female prisoners. The research method used is literature review, by tracing related research to strengthen research results.